PELATIHAN TEKNIK ECOPRINT DENGAN PEMANFAATAN BAHAN ALAM UNTUK MENINGKATKAN KREATIVITAS MASYARAKAT DESA BECIRONGENGOR - Satrio Wibowo; Mochammad Ludfy Hadist Maghfiro; Aulia Fitriany; Dwi Novela Roehmatulloh; Marinda Alfionita; Kharitsatul Khusnah; Ahmad Arka Yuningrat (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2024)
Ecoprint bags can be used as a lifestyle for the community because ecoprint uses leaves and flowers that come from nature. The purpose of this community service activity is that PKK mothers can add insight and creativity, starting from the introduction of plants and how to make ecoprints. The purpose of the introduction of ecoprint is to provide knowledge in utilizing plants. The method used is practice and evaluation, in the final result the totebag bag gets maximum results. The evaluation used direct observation of the totebag ecoprint products made by the PKK women. PKK women are able to print motifs and colors from leaves and flowers on the appropriate totebag bag